Bicycle lane priority: Promoting bicycle as a green mode even in congested urban area. (May 2016) - Bagloee, Saeed Asadi; Sarvi, Majid; Wallace, Mark
Highlights: Lanes dedicated to bicycle in the heart of the congested cities are sought. We employed the Braess Paradox (BP): Roads infected by BP is found and marked as bicycle lanes. Shared bicycle scheme, electric-bike and integration to the public transport system are also discussed. Real network of the city of Winnipeg, Canada is our pilot study. Article appeals to traffic authorities, policy makers, practitioners and planner as well as scholars. Abstract: The main obstacles to boosting the bicycle as a mode of transport are safety concerns due to interactions with motorized traffic. One option is to separate cyclists from motorists through exclusive bicycle priority lanes. This practice is easily implemented in uncongested traffic. Enforcing bicycle lanes on congested roads may degenerate the network, making the idea very hard to sell both to the public and the traffic authorities. Inspired by Braess Paradox, we take an unorthodox approach to seeking latent misutilized capacity in the congested networks to be dedicated to exclusive bicycle lanes. The aim of this study is to tailor an efficient and practical method to large size urban networks. Hence, this paper appeals to policy makers in their quest to scientifically convince stakeholder that bicycle is not a secondary mode, rather, it can be greatly accommodated along with other modes even in the heart of the congested cities. In conjunction with the bicycle lane priority, other policy measures such as shared bicycle scheme, electric-bike, integration of public transport and bicycle are also discussed in this article. As for the mathematical methodology, we articulated it as a discrete bilevel mathematical programing. In order to handle the real networks, we developed a phased methodology based on Branch-and-Bound (as a solution algorithm), structured in a less intensive RAM manner. The methodology was tested on real size network of city of Winnipeg, Canada, for which the total of 30 road segments – equivalent to 2.77 km bicycle lanes – in the CBD were found.